Meningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Mencetak Gambar Berpola Dengan Media Buah Belimbing Pada Kelompok A Di TK. Melati Tanjung Selor Hulu Tahun Pelajaran 2020/2021 - Supianty, Andi Erna; Sjamsir, Hasbi (Manajemen Pendidikan Program Doktor, 2022)
This study aims to determine the stages of development and improve fine motor skills in early childhood 4-5 years by printing patterned images with star fruit media. The subjects of this study were group A Tanjung Selor TK.Melati students. This research method is in the form of creativity to motivate the improvement of fine motor skills in early childhood through printing activities. The results of increasing creativity and fine motor skills in early childhood through printing activities carried out by using sponge media and star fruit to print patterned images are shown by achieving the following scores: Pre-Cycle Actions 33%, Cycle I Actions reaching 46%. And in Action Cycle 2 it reaches 81%.